2017
DOI: 10.1016/j.jcol.2016.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's disease: risk factor for colorectal cancer

Abstract: Background Crohn's disease is an inflammatory disease that can reach any part of the gastrointestinal tract. This disease has been associated with an increased neoplastic risk, including colorectal carcinoma. Objective The objective of this work is to describe the mechanisms present in two diseases, and that are responsible for the increased risk in Crohn's disease. Methods A bibliographic research was conducted in PubMed database. In addition to the articles obtained with an inserted query… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
4
0
1
Order By: Relevance
“…and Enterobacteriaceae ( Escherichia coli ), which as previously described may contribute to colorectal carcinogenesis [ 63 , 64 , 65 ]. Indeed, several recent studies have shown associations between colorectal cancer and CD activity [ 66 , 67 , 68 ] although a direct cause has not yet been demonstrated. The implication of gut microbiota in the link between CD and cancer would be immense, particularly for microbiota-based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…and Enterobacteriaceae ( Escherichia coli ), which as previously described may contribute to colorectal carcinogenesis [ 63 , 64 , 65 ]. Indeed, several recent studies have shown associations between colorectal cancer and CD activity [ 66 , 67 , 68 ] although a direct cause has not yet been demonstrated. The implication of gut microbiota in the link between CD and cancer would be immense, particularly for microbiota-based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…It was already known that chronic inflammation creates a microenvironment suitable for the disease progression [33]. dosSantos [34], has identified that a pro-inflammatory state is the cornerstone in the association between CD and CRC, justifying the fact that CD might be a risk factor for CRC. She added that a family history of CRC is an important factor that doubles the risk of CRC in patients with CD.…”
Section: Discussionmentioning
confidence: 99%
“…This can be inferred from the association between chronic inflammatory diseases, such as inflammatory bowel disease and Crohn’s disease, and increased risk for colorectal cancer. 66,67 Obesity is also associated with chronic inflammation, which may play a role in the efficacy of aspirin in preventing colorectal cancer. Rothwell and colleagues recently investigated the effect of aspirin on the risk of cardiovascular events and cancer in a collective of randomized trials and found that the preventative effect of aspirin on cancer risk is dependent upon bodyweight and dose.…”
Section: Introductionmentioning
confidence: 99%